The economic impact of the little ice age - Morgan Kelly; Cormac Ó Gráda (University College Dublin, UCD School of Economics, 2010)
We investigate by how much the Little Ice Age reduced the harvests on which pre-industrial Europeans relied for survival. We find that weather strongly affected crop yields, but can find little evidence that western Europe experienced long swings or structural breaks in climate. Instead, annual summer temperature reconstructions between the fourteenth and twentieth centuries behave as almost independent draws from a distribution with a constant mean but time varying volatility; while winter temperatures behave similarly until the late nineteenth century when they rise markedly, consistent with anthropogenic global warming. Our results suggest that the existing consensus about a Little Ice Age in western Europe stems from a Slutsky effect, where the standard climatological practice of smoothing data prior to analysis induces spurious cyclicality in uncorrelated data.
hdl:10197/2649
Keywords: 330